2018
DOI: 10.1002/aenm.201703392
|View full text |Cite
|
Sign up to set email alerts
|

Mixed 3D–2D Passivation Treatment for Mixed‐Cation Lead Mixed‐Halide Perovskite Solar Cells for Higher Efficiency and Better Stability

Abstract: Layered low‐dimensional perovskite structures employing bulky organic ammonium cations have shown significant improvement on stability but poorer performance generally compared to their 3D counterparts. Here, a mixed passivation (MP) treatment is reported that uses a mixture of bulky organic ammonium iodide (iso‐butylammonium iodide, iBAI) and formammidinium iodide (FAI), enhancing both power conversion efficiency and stability. Through a combination of inactivation of the interfacial trap sites, characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
218
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(229 citation statements)
references
References 61 publications
10
218
0
1
Order By: Relevance
“…[23,[33][34][35][37][38][39][40] In addition, the easy oxidation of Sn and Ge from the +2 state to the +4 state due to their high energy 5s and 4s orbitals makes them less promising for application in stable and long-term PSCs. [49] However, the highest certified PCE in a 2D-only planar PSC is 15.3%, [50] which is far below that of their 3D perovskite-based counterparts. [42,43] Furthermore, low dimensional (e.g., 2D, 1D, and 0D) perovskites have also been used to address the stability issues in PSCs.…”
mentioning
confidence: 99%
“…[23,[33][34][35][37][38][39][40] In addition, the easy oxidation of Sn and Ge from the +2 state to the +4 state due to their high energy 5s and 4s orbitals makes them less promising for application in stable and long-term PSCs. [49] However, the highest certified PCE in a 2D-only planar PSC is 15.3%, [50] which is far below that of their 3D perovskite-based counterparts. [42,43] Furthermore, low dimensional (e.g., 2D, 1D, and 0D) perovskites have also been used to address the stability issues in PSCs.…”
mentioning
confidence: 99%
“…The increased R ct and R rec of 2D/3D MHP indicated the roles of 2D MHPs in passivating surface traps and improving charge transfer . Similarly, other 2D MHPs including (i‐BA) 2 PbI 4 , (AVA) 2 PbI 4 , and MA 3 Bi 2 I 9 were also produced on 3D MHPs and exhibited improved performance and stability …”
Section: Interfacial Modification Layersmentioning
confidence: 89%
“…XRD measurement is a structure‐monitoring method used to investigate the effect of interface engineering on the stability of the MHP layer. For example, XRD was used to demonstrate the excellent moisture stability of MHPs after 2D MHP interface modification by monitoring PbI 2 and yellow phase characteristic patterns …”
Section: Interface Characterizationsmentioning
confidence: 99%
“…a) The J-V curve of the champion devices in small size (0.0737 cm 2 ) measured from reverse and forward scan. [73] Copyright 2018, John Wiley & Sons. Reprinted with permission from Ref.…”
Section: Surface Passivation By Organic Halide Saltmentioning
confidence: 99%
“…2019, 2, 93-106 of FAPbBr 3-x I x was formed after reaction with the excess of PbI 2 present on the surface. [73] Wang et al reported growth of 2D PEA 2 PbI 4 capping layers on top of 3D perovskite film, which resulted in an enhanced Voc and drastically improved the stability of PSCs without compromising their high performance ( Figure 12b). The preparation method is shown in Figure 12a.…”
Section: Surface Passivation By Organic Halide Saltmentioning
confidence: 99%